The contemporary reform of global financial governance : implications of and lessons from the past - Helleiner, Eric (UN New YorkUS, 2009)
Argues that officials will need to think more creatively and ambitiously about international financial reform than they have done so far if they are to claim the mantle of the 1944 Bretton woods conference.